2020
DOI: 10.1038/s41598-020-78842-w
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and functional capacity of centenarians

Abstract: The number of very old individuals, namely centenarians, is growing fast. In dentistry, the increasing number of older adults retaining natural teeth present new challenges for preventive and restorative dental care. However, there is a considerable lack of knowledge on the oral health status and needs in this exceptional age group. The aim of this population-based study was to identify the prevalence of oral diseases, therapeutic needs and functional capacity (evaluating centenarians’ autonomy and their capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The included studies reported caries prevalence or experience of older adults at the age of 60 or above in 20 countries from six continents (Table 1). Most of them were conducted in Asia (n = 20, China [11][12][13][14][15][16], India [17][18][19][20][21][22][23][24], Singapore [25], Turkey [26][27][28][29][30][31][32][33][34][35][36][37][38] and Vietnam [29,30]) and Europe (n = 10, Finland [31], Germany [32,33], Ireland [34], Kosovo [35], Norway [36], Poland [37,38], Portugal [39] and Romania [40]). There were three studies conducted in North America (Mexico [41,42] and USA [43]), one in South America (Brazil [44]), two in Oceania (Australia [45,46]) and three in Africa (...…”
Section: Resultsmentioning
confidence: 99%
“…The included studies reported caries prevalence or experience of older adults at the age of 60 or above in 20 countries from six continents (Table 1). Most of them were conducted in Asia (n = 20, China [11][12][13][14][15][16], India [17][18][19][20][21][22][23][24], Singapore [25], Turkey [26][27][28][29][30][31][32][33][34][35][36][37][38] and Vietnam [29,30]) and Europe (n = 10, Finland [31], Germany [32,33], Ireland [34], Kosovo [35], Norway [36], Poland [37,38], Portugal [39] and Romania [40]). There were three studies conducted in North America (Mexico [41,42] and USA [43]), one in South America (Brazil [44]), two in Oceania (Australia [45,46]) and three in Africa (...…”
Section: Resultsmentioning
confidence: 99%
“…In our study cohort, notably limited by its relatively small sample size, OHRQoL was not influenced by the question of institutionalization, nursing care or mental state, which are factors that have been shown to have an influence in studies with younger participants. We have previously shown that these factors also had no impact on centenarians’ cariological or periodontal status [ 33 , 34 ]. At the age of 100 years and older, all participants received some kind of help or nursing care, whether at home or in a care facility; this may have alleviated differences.…”
Section: Discussionmentioning
confidence: 99%
“…Since older adults, especially centenarians, are often reduced in their mobility, access to dental care is limited [ 46 ]. Only approximately half take part in regular check-ups [ 34 ] and, due to their lower resilience, dentists may opt for uncomplicated, sometimes provisional care, possibly causing the relatively high prevalence of denture sores by these means.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Centenarians may also have different oral hygiene behaviors compared with other groups of people. Many may decrease toothbrushing frequency or lose the ability to perform oral hygiene independently because of functional and cognitive impairment [ 35 , 36 , 37 ]. However, some may maintain this lifelong oral hygiene practice.…”
Section: Introductionmentioning
confidence: 99%